The green credit policy and the ESG performance of heavily polluting enterprises in China - Jia, Guiqiong; Bai, E. (Frontiers in Earth Science, 2025)
The Green Credit Policy is a crucial tool for driving the transformation and upgrading of heavily polluting enterprises and protecting the environment. By employing a difference-in-differences (DID) approach to construct a quasi-natural experiment, this paper examines the impact of the policy on the ESG (Environmental, Social, and Governance) performance of heavily polluting enterprises. The results indicate that the policy significantly improves the ESG performance of these enterprises, and this finding remains robust after a series of robustness tests. Additionally, the policy exhibits a “long-tail effect,” meaning its positive impact extends through 2021. Furthermore, panel quantile regression results reveal that the policy has a more pronounced positive impact on enterprises with poorer ESG performance. The study also shows that foreign-owned and mixed-ownership enterprises, as well as larger firms in employee size, do not benefit from the policy, whereas other companies do experience positive effects. Finally, the moderating effect analysis indicates that the age of senior management negatively moderates the policy’s impact, while executives with a financial background and effective internal control systems positively moderate its effects. This paper provides a new perspective for future research on corporate ESG performance and offers theoretical insights for the refinement of future policies.